Potensi Inovasi pada Instrumen Keterampilan Proses Sains: Studi Literatur - Asyrifah Nur Qalby; Eda Lolo Allo; Dewiyanti Fadly (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
Science Process Skills (SPS) are the skills of scientists in investigating phenomena, developing concepts, and solving problems that serve as a foundation for students to fully understand scientific literacy. This study aims to conduct a literature review regarding innovations in integrating socio-scientific issues into science process skills instruments. This study is a qualitative study using the Systematic Literature Review method that reviews accredited articles relevant to the research topic. Data analysis techniques used include data collection from various journals, data reduction processes, descriptions, verification, and conclusions. The results of the article review indicate that extensive development of SPS instruments has been conducted. However, a research gap remains that a SPS instrument that specifically integrates Socio-Scientific Issues has not yet been found. Existing instruments generally still focus on purely cognitive aspects without involving controversial and contextual socio-scientific issues.